Letter to Jane Tolmach in support of Adlai Stevenson for President - Esther Goodhue::::::; Donald Goodhue::::::; Dorothy Hall::::::; Gordon Hall:::::: (1960)
A letter to Jane Tolmach from Hall and Goodhue, Architects and Planners, in support of Adlai Stevenson for President.